PANDANGAN AL-SYATIBI TENTANG MAQASID AL-SYARI’AH - Syahabudin Syahabudin (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2014)
According to Islamic law thinking perspective, the experts of Ushul Fiqh apply a number of various methods in doing ijtihad, such as Qiyas, Istihlah, Istishab, and ‘Urf. The application of those methods is also based on Maqasid Al-syari’ah. The study of Maqasid Al-syari’ah is very essential for the effort of law ijtihad because it can be the basis of law establishment. This consideration becomes a requirement for several problems in which their explicitness cannot be found in Nash. This article tries to analyze the concept of Maqasid Al-syari’ah according to al-Syatibi.ملخص: وفىتفكيرالحكم الاسلامى, قدطبق الاصوليون القواعد اوالمناهج المتنوعة فىالاجتهاد ومن تلك القواعد هى: القياس والاستصلاح والاستصحاب والعرف وغيرها. والجدير بالمعرفة ان تطبيق تلك القواعد اوالمناهج فىاستنباط الاحكام يستند الى مقاصد الشريعة. فبذالك, كانت مهمة للغاية فىمحلية الاجتهاد. وهذ الاعتبار يكون لازماللمسائل التى لاتوجد معناها فىالنص وضوحا. وهذه المقالة تشرح شرحاعميقا عن فكرمقاصدالثريعة عندالشاطى.